2009
DOI: 10.1021/jo9011199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ring Size on theExo/EndoSelectivity of a Thermal Double Cycloaddition of Fused Pyran-2-ones

Abstract: A study of an unusual effect of the size of the ring fused to 2H-pyran-2-ones on the exo/endo selectivity of a thermal double cycloaddition of N-substituted maleimides or maleic anhydride yielding bicyclo[2.2.2]octene derivatives is presented. With subtle variations of starting compounds and reaction conditions exclusively exo,exo or exo,endo products can be prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…7.5 Hz), we can conclude that the bicyclo[2.2.2] octene fragment is of the symmetric exo,exo structure, also consistent with our previous results. 30 Furthermore, a singlet at δ 6.82 (for 2H) corresponding to both protons attached to the double bond of the bicyclo[2.2.2]octene fragments and a singlet at δ 8.43 (for 2H) for the two NH groups were also observed in 1 H NMR. In the IR spectrum of 3 bands corresponding to the NH group at 3368 cm -1 and carbonyl group at 1698 cm -1 were observed.…”
Section: Synthesismentioning
confidence: 93%
See 1 more Smart Citation
“…7.5 Hz), we can conclude that the bicyclo[2.2.2] octene fragment is of the symmetric exo,exo structure, also consistent with our previous results. 30 Furthermore, a singlet at δ 6.82 (for 2H) corresponding to both protons attached to the double bond of the bicyclo[2.2.2]octene fragments and a singlet at δ 8.43 (for 2H) for the two NH groups were also observed in 1 H NMR. In the IR spectrum of 3 bands corresponding to the NH group at 3368 cm -1 and carbonyl group at 1698 cm -1 were observed.…”
Section: Synthesismentioning
confidence: 93%
“…[27][28][29][30][31] Namely, it was already observed that 2H-pyran-2-ones can act as "double" dienes, reacting in two consecutive Diels-Alder reactions with two distinctive molecules of the dienophiles, yielding bicyclo[2.2.2]octenes. 30 The initial cycloaddition step leads to the formation of CO 2 -bridged oxabicyclo[2.2.2]octenes that in the next step eliminate a molecule of CO 2 (via a retro-hetero-Diels-Alder reaction) providing cyclohexadiene systems that act as new dienes for another molecule of dienophile finally providing the double cycloadducts. On the other hand, if the two molecules of the dienophile would be connected by a suitable tether, it would be possible to expect that the second cycloaddition step would take place intramolecularly.…”
Section: Synthesismentioning
confidence: 99%
“…This type of symmetric product is in agreement with the expected stereostructures of the energetically favored transition states. 37 However, in special cases where severe steric hindrance exists between the two reacting partners, it was suspected that the second cycloaddition step could take place via a different stereochemical course. Indeed, such asymmetric endo,exo-bicyclo[2.2.2]octenes 50 were obtained when an eight-membered ring was fused to the starting 2H-pyran-2-one skeleton (i.e.…”
Section: Scheme 14mentioning
confidence: 99%
“…We found that the methyl substituent (49, R = Me) was the smallest among those examined, to provide such an effect (Scheme 15). 37 In contrast, when maleic anhydride (51) cycloadded to the fused 48, symmetric exo,exo adducts 52 were again produced, clearly demonstrating the need for both partners to provide sufficient steric hindrance during the stereochemically crucial reaction step and consequently to change the stereoselectivity of the bicyclo[2.2.2]octene adduct (Scheme 15). Previously such asymmetric endo,exo products were accessible only via photochemical conditions.…”
Section: Scheme 14mentioning
confidence: 99%
“…Besides alkynes [4][5][6][7][8][9][10][11], alkenes [12][13][14][15][16][17][18] can also be used as dienophiles in Diels-Alder reactions: the CO 2 -bridged cycloadduct (7-oxabicyclo[2.2.2]octene) that is formed in the first reaction step when the diene is the pyran-2-one scaffold is not usually stable under thermal reaction conditions, and eliminates CO 2 via a retroDiels-Alder reaction, forming a new cyclohexadiene system that can either act as a new diene for a new DielsAlder reaction or alternatively (when appropriate groups for elimination are present) aromatize into a benzene system.…”
Section: Introductionmentioning
confidence: 99%